Relationships between the advertising appeal and behavioral intention: the mediating role of the attitude towards advertising appeal - Raza, Syed Hassan; Abu Bakar, Hassan; Mohamad, Bahtiar (EDP Sciences, 2017)
The link between the advertising appeal, attitude and behavioral intention is dynamic in nature, however, little research has been pursued towards explaining the mediating role of attitude towards the advertising in link of the advertising appeal with the behavioral intention. Researchers have identified the importance of the attitude in the connection of the advertising appeal within the framework of the (TPB) which remains unaddressed in the explicating the mediation of the attitude in relationship of advertising appeal and behavioral intention.This paper aims to provide insight of the attitude towards the advertising as the mediating factor in explaining the relationship between the advertising appeal and behavioral intention.In addition, this paper is only a theoretical exploration, it is expected that this work lead towards an explanation of the mediating role of the attitude to address the relation of advertising appeal and intention which may be studied further to determine the empirical finding about the other dynamic of the (TPB).